KOMUNIKASI INTERPERSONAL DA’I PENDAMPING ANAK JALANAN DI RUMAH SINGGAH SALVATORE SURABAYA - Millenia Prihatini; Abdul Muhid (Jurnal Dakwah Risalah, 2019)
The phenomenon of street children is a problem that needs to be dealt with a companion da’i at the Salvatore Surabaya shelter through a humanistic approach who goes straight of accompanying and invites a positive direction in shaping his self-concept. The purpose of this study is to describe the interpersonal communication of escorts and street children. This research is a descriptive qualitative study using observation techniques, in-depth interviews and data validity using source triangulation. The results of this study are that the assistant can be able to build openness with street children through interpersonal communication inviting to communicate with being guided, being approached to find out what is happening to street children, and empathize to feel like street children experience. Supporting attitude from the companion invites discussion and talks about the hobbies of street children. The positive attitude of interpersonal communication from the companion da’i with street children in interacting is also able to put themselves in the position of friends and parents.